Gaya Belajar pada Siswa SMA di Sekolah Alam Sriwijaya Palembang - Putra, Firza Anugra; Budiman, Budiman (Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, Sumatra Selatan, 2021)
This study discusses the learning styles for high school students at Sriwijaya Nature School Palembang. This study uses a qualitative method with a descriptive design. The subject selection technique used purposive sampling with criteria, aged 16-17 years, 11th grade high school students, domiciled in Palembang. Methods of data collection using interviews, observation, and documentation. The results of the study generally show that the three subjects (DY, EN, NA) have a picture of the learning styles. the three subjects, namely DY, EN, and NA have similarities in the learning method section. The subject chose the outdoor method as the most preferred method. In addition, there are several factors that influence the implementation of learning styles for high school students at Sriwijaya Nature School Palembang namely interactions between friends, learning experiences, preferred subjects, emotions in the learning process, and ideals/professions of interest.